The Use of ICT in ELT: How Teacher Should Be Empowered - Arni Fitri; Abdul Aziz Rifa'at (Institut Agama Islam Negeri Palopo, 2021)
ICT has the potential to “bridge the knowledge gap” in terms of improving quality of education, increasing the quantity of quality educational opportunities, making knowledge building possible through borderless and boundless accessibility to resources and people, and reaching populations in remote areas to satisfy their basic right to education. This article presents on how to empower teacher in ELT through ICT. The fact that not all teacher of English in Indonesia are master in ICT, there are some teacher poor in ICT. Teachers’ computer literacy is 54.2%, teacher own internet literacy is 51.4%, teacher current typing skill is 51.4%. This article also present the advantages of ICT in ELT, they are: 1) keeping up with the world, 2) Bringing variety t your work, 3) breaking the routine, 4) getting new experience, 5) being creative and 6) meeting your learners. Empower teacher through ICT refers to a process that includes any communication device or application, which people become powerful enough to engage in, share control of, and influence events and institutions affecting their lives. Empowerment processes through ICT includes 1) teacher professional development such workplace training, seminar, professional meeting; 2) teacher technology management.